지역사회 거주 복합만성질환 노인의 약물복용이행 관련 요인 - 김정선(Kim, Jeong Sun) (Nursing and Health Issues(간호와 보건연구), 27(1), 2022)
Purpose: Changes in the rapidly increasing older population has led to increase prevalence of chronic diseases. This purpose of this study was to identify factors associated with medication adherence among the elderly with multimorbiditiy in a community-dwelling. Methods: This was a descriptive study, including 250 older people over 65 years with multimorbiditiy in G city. Data were analyzed using SPSS Statistics 27.0 to obtain descriptive statistics, independent t-test, one-way ANOVA, Pearson’s correlation coefficient and a stepwise multiple linear regression. Results: The mean scores of medication adherence were 6.43±1.75, 72 (28.8%) in a low level, 80 (32.0%) in a medium level, and 98 (39.2%) in a high level. There were significant correlations between subjective memory complaints (r=.23, p<.001), depression (r=−.33, p<.001), social support (r=.26, p<.001), self-efficacy (r=.18, p=.001) and medication adherence. Depression (=−.28, p<.001), recognition of medications taken (=.23, p<.001), alcohol consumption (=.12, p=.040), number of chronic diseases (=.14, p=.014) and access to medical institutions (=.13, p=.032) significantly influenced medication adherence, and the overall explanatory power was 19.2%. Conclusion: The results suggested that evidence to evaluate in detail the factors related to medication adherence when monitoring the comprehensivehealth assessment and medication management status of the elderly with multimorbiditiy in primary health care settings, and to provide evidence of an integrative system development in medication management and nursing intervention strategies that can make medication adherence practice a daily life. KCI Citation Count: 1